Extra-Poliical Analysis of Interethnic Relations - Reshetnikov, Mikhail (Advances in Social Sciences Research Journal, 2023)
The article discusses the main psychological mechanisms that contribute to the formation of interethnic conflicts. The author describes the following psychological phenomena: historical mental trauma inflicted by a hostile group; narcissism of small differences; identification with the aggressor; transmission of traumatic experiences to the next generations; division of all ideas and all people into ‘we’ and ‘they’; importance of culture and language in the formation and personality’s social functioning. The conclusion substantiates an original hypothesis about the intensification of interethnic conflicts around the world in the twenty-first century.